The pattern of traditional and modern bone setting among the people in a selected community in Kano, Nigeria: a comparative study - Salihu, Muhammad Nuhu; Lawal, Mamman Muhammad; Musa, Abuhuraira Ado; Adigun, Waheed Taoreed; Muhammad, Faisal (International Surgery Journal, 2021)
Background: Bone setting practices contribute largely to alternative medicine almost all over the world. It’s commonly accessible in large parts of rural populations. The aim of the study was to determine the pattern of traditional and modern bone settings among the people in a selected community in Kano, Nigeria. Methods: The study was a descriptive cross-sectional type of study carried out from January to May 2019 to determine the pattern of traditional and modern bone (TBS and MBS) settings among the people residing in Kano, Nigeria. A simple random sampling technique was used to select a total of 222 study participants from the selected community. In this study, a face-to-face interview technique was used to collect the information from the study participants using a semi-structured questionnaire. The data were analyzed using a statistical package for social sciences (SPSS) 22.0 version. Results: In this study, about 34.7% were between 31-35 years and most of the respondents (28.4%) had secondary school level of education. Slightly above nine-tenths (90.1%) of the respondents stated that TBS is more preferable than MBS and the reason for preference were fear of amputation/operation (51.0%), lack of knowledge (32.0%), the attitude of health personnel (28.0%) and fear of the application of plaster of paris (25.0%). Conclusions: The finding of this study reveals more than half of the respondents had enough knowledge of both traditional and modern bone settings. The public should be educated about the modern method of bone setting and the complications of traditional bone setting.